From the Chair (Historia, 2021)
EnglishThis year marks the 60th year of the formation of the Historical Society of South Africa. In typical historical fashion this calls for some form of commemoration, if not reflection, on a historic milestone of both the society as well as its journal. After all, jubilees, anniversaries and centennials of human beings, human associations and human structures, call for some form of acknowledgement and are often cause for recourse to some form of historical pondering. Most times these are reflections that celebrate an unchallenged past, one where the story is sanitised and the past is venerated. HASA and Historia are no exception. Its forefathers (few foremothers) occasionally took stock of what had been achieved on a surprisingly intermittent basis. At the risk of committing the historical sin of over-simplification and generalisation, as well as being constricted by the editorial word limit, I briefly peruse the tangible voice of HASA in its journal, Historia. It is thus to the past that this brief presidential note turns, while Historia's editor-in-chief and the editorial board look to its future.   AfrikaansDie Historiese Genootskap van Suid-Afrika teken hierdie jaar sy 60ste kerf aan. Dit is dus, eie aan die geskiedkundige gebruik, die gepaste geleentheid vir 'n oordenking - oftewel 'n besinning - oor 'n historiese mylpaal vir die genootskap en sy joernaal. Jubileums, herdenkings en eeufeeste, hetsy van mense, menslike genootskappe of mensgemaakte strukture, vereis 'n mate van erkenning en lei ook dikwels tot historiese bepeinsing. Só 'n besinning kan ook ontaard in die viering van 'n onbestrede verlede, 'n witgekalkte verhaal, of 'n geroemde geskiedenis. Wat dit betref is die HGSA en Historia hoegenaamd nie 'n uitsondering nie. Sy voorvaders (daar was weinig voormoeders) het van tyd tot tyd - oftewel elke dan en wan - bestek geneem van alles wat vermag is. Sonder om die gevaar te loop om die historiese aardsondes van oorvereenvoudiging en veralgemening te pleeg, en gedagtig aan die redaksionele woordbeperking, wil ek nogtans die HGSA se tasbare stem vanuit sy joernaal, Historia, laat opklink. Hierdie kort voorsittersboodskap is dus op die verlede gemik, terwyl Historia se hoofredakteur en redaksionele raad hul blik op die toekoms rig.